Could anthropic pressures drive the burrowing behavior of sandy beaches species? An investigation on Atlantorchestoidea brasiliensis (Amphipoda: talitridae) - Abude, Rayane R. S.; Ribeiro, Yuri S. F.; Augusto, Matheus; Cabrini, Tatiana M. B. (Frontiers in Marine Science, 2023)
Animal behavior represents the connection between individuals and their environment. Environmental conditions on sandy beaches determine the presence, demographic characteristics, and life history of benthic macrofaunal species. The expression of agile behaviors on sandy beaches is a key factor given the rapid environmental changes. Atlantorchestoidea brasiliensis is a sandhopper crustacean, a bioindicator for sandy beach quality, which usually builds burrows along the intersections of wet and dry sand. This study aimed to evaluate differences in the burial depth of A. brasiliensis in regions with and without anthropogenic interactions. We hypothesize that the sandhopper buries further deep on beaches with greater human interference as a behavioral adaptation to avoid direct human interaction. Samples of the A. brasiliensis burrows and data on their burial depths were collected from four beaches in Rio de Janeiro, two with free access to people and two with restricted access. Environmental variables were determined and their influence on burial depth was tested using a Generalized Linear Model. Generalized Additive Models were used to test the occurrence of individuals at each burial depth in the two beach situations. No clear relationship was observed between the environmental variables and burial depth whereas, deeper burials were observed only on free access beaches. The results obtained substantiate the initial hypothesis. The present study is thus an initial step towards further research on changes in the pattern of animal behavior induced by direct anthropogenic pressures on sandy beaches.